Midwives as Navigators: An Appreciative Inquiry Into the Work of Hospital Midwives in New Zealand - Walker, Tracy (Auckland University of Technology, 2025)
This study asks the question: What is the work of core midwives and what facilitates their role in New Zealand’s large hospitals? Core midwives, a term specific to New Zealand for employed hospital midwives, are described as integral to or the “backbone of New Zealand maternity service” (Gilkison, 2017, p. 36). The 2024 Midwifery Workforce Survey conducted by the New Zealand Midwifery Council highlighted this pivotal role with 48.1% (1,618/3,364) of midwives identifying core midwifery as their main source of work. This compares with 32.6% (1,095/3,364) of midwives identifying caseloading as their primary role which includes both employed and self-employed as lead maternity carers (community caseloading midwives). Despite their unique contribution to the midwifery profession, core midwives perceived themselves as ‘just a core midwife’ and feel as ‘invisible’ (Gilkison et al., 2017). These perceptions warrant exploration and comprehension of the work and role of core hospital midwives. This Appreciative Inquiry study, with a hermeneutics lens, explores the everyday work of core midwives within New Zealand’s large secondary/tertiary hospitals, and what facilitates their role. Fourteen core midwives from New Zealand participated. The study found that core midwives could be described as ‘navigators’. Midwives in this study described their unique skillset which enabled them to work in partnership with the women in their care and navigate the often-complex care that women required. To be an effective navigator, the core midwife needs to be able to communicate well with women and their families, cultivate effective collegial relationships, and foster teamwork. This research is important because it brings perspective to the significant role that core midwives play, enriching understandings of maternity care provision and acknowledging the support for safeguarding core midwives’ well-being who, at their ‘core’, safeguard the lives of women and their babies.